Vocabulario Pai Tavyterã Guaraní (Journal on studies and research of academic knowledge, 2019)
This article resumes the first findings based on a pai tavyterã guaraní corpus of 621 lexemes collected in fieldwork. These results are a reflection of the exhaustive work done classifying, analyzing, describing and translating Pai Tavyterã Guaraní linguistic documentary material compiled for over 40 years of fieldwork (1978-present). The goal of this documentary lexicographic work, in first instance, was to register this Guaraní lexis, which constitutes the third most spoken Guaraní in Paraguay with approximately 15.000 speakers. However, this lexeme database is also useful to sustain this Guaraní’s differences and specificities in comparison to others spoken in the region. Thus, the purpose of this research is to become an indigenous language document of linguistic enquiry and reference, as well as, a database with empirical facts scientifically sustained to show the particularities of a guaraní spoken by a minoritarian indigenous group in Paraguay.
Keywords: Pai Tavyterã Guaraní; Lexicography; Documentation of an indigenous language; Language Endangerment